?Effect of a Synthetic Pheromone When Applied to Different Models on Male Mating Behaviour in Musca domestica (Biological Sciences - PJSIR, 1994)
consiousness and the acetone solvent could evaporate fromall. The treated flies were marked with a white spot (vinylmatt emulsion, lily white colour) on the thorax to distinguishthem from the control ones.